Analysis of pharmacokinetics and PK/PD parameter Cmax/MIC for ciprofloxacin in patients with neutropenic fever - Szałek, Edyta; Kamińska, Agnieszka; Łojko, Anna; Grześkowiak, Edmund; Komarnicki, Mieczysław; Murawa, Dawid; Nabywaniec, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2010)
Background: The antimicrobial efficacy of chemotherapeutics is determined by their pharmacokinetic/pharmacodynamic properties (PK/PD). To estimate the efficacy of an antibiotic therapy three basic markers were established: the ratio between peak antibiotic concentration obtained after a single dose and the minimum inhibitory concentration (Cmax/MIC) for e.g. fluoroquinolones, the ratio between the area under the curve of serum concentration within the 24-hour time limit and MIC (AUC24/MIC) for e.g. tetracyclines, and the time when the concentration remains above the MIC (T > MIC) for e.g. -lactams. Aim of study: The aim of the study was to analyse the pharmacokinetics and PK/PD parameter Cmax/MIC for ciprofloxacin in patients with neutropenic fever. Material and methods : The study was conducted on 6 patients with neutropenic fever with identified bacteria, hospitalized because of multiple myeloma (n = 4), non-Hodgkin lymphoma (n = 1), or acute granulocytic leukaemia (n = 1). The patients were treated with ciprofloxacin in the dose of 200 mg/12 h ( i.v. ). Plasma concentrations of ciprofloxacin after the first dose (Cmax1) and at steady state (Cssmax, Cssmin) were measured by a validated HPLC method with UV detection. Results : The maximum concentrations after the first dose (Cmax1) (mean ± standard deviation) and the maximum and minimum concentrations at steady state were Cmax1 = 1.620 (± 1.050) µg/ml, Cssmax1 = 2.087 (± 0.990) µg/ml, Cssmin = 0.618 (± 0.602) µg/ml. The mean Cmax1/MIC ratio and Cssmax/MIC were: 1.241 (± 1.341) and 2.183 (± 2.274). Conclusions: The low values of Cmax/MIC for ciprofloxacin in the analysed patients indicate too low drug concentrations in the blood in comparison with the MIC of pathogens and the need of PK/PD monitoring in order to carry out initial evaluation of the applied treatment and to verify the established dosing regimen.